Yin-yang framework of decision-making: Development and assessment of Yin-yang decision-making styles questionnaire. (April 2023) - Ding, Cody; Fung, Hung-Gay; Zhang, Yan
Abstract: Decision-making styles represent the typical manner individuals use to make decisions. This study aimed to develop and test the structure of a decision-making style questionnaire based on the Yin-yang framework of decision making. Two studies were carried out. In Study 1, we generated an initial item pool of 122 items using a theory-driven approach. Then three focus groups were used to finalize 54 items for the field testing. Third, using a hybrid of iterative exploratory factor analysis and ant colony optimization approach ( n = 895), we identified 23 items that were deemed best to represent five constructs of the yin-yang framework of decision making: adaptability, relative positioning, self-awareness, proactivity, and prudence. In Study 2, we performed the validation study ( n = 569) by testing three models of the yin-yang framework of decision making styles. We also explored age and sex differences. The results from two studies provide initial support for the factor structure and reliability of the Yin-yang decision-making questionnaires. The results were discussed in the context of the yin-yang framework and age and sex differences regarding these constructs. Highlights: The Yin-yang framework of decision-making is used as a theoretical perspective. Iterative EFA and Ant colonization optimization used for instrument development. Confirmatory analysis was conducted to test three models of the 23-item instrument. Age and sex differences regarding Yin-yang decision-making styles were examined. A promising decision-making style instrument from an eastern cultural perspective